Disease activity assessment in childhood vasculitis: development and preliminary validation of the Paediatric Vasculitis Activity Score (PVAS). Issue 10 (25th October 2012) - Dolezalova, Pavla; Price-Kuehne, Fiona E; Özen, Seza; Benseler, Susanne M; Cabral, David A; Anton, Jordi; Brunner, Jürgen; Cimaz, Rolando; O'Neil, Katheleen M; Wallace, Carol A; Wilkinson, Nicholas; Eleftheriou, Despina; et al.
Abstract : Background: Rare chronic childhood vasculitides lack a reliable disease activity assessment tool. With emerging new treatment modalities such a tool has become increasingly essential for both clinical practice and therapeutic trials to reproducibly quantify change in disease state. Objective: To develop and validate a paediatric vasculitis activity assessment tool based on modification of the Birmingham Vasculitis Activity Score (BVASv.3). Methods: A paediatric vasculitis registry was reviewed to identify clinical features missing in the BVASv.3. A modified nominal group technique was used to develop a working version of the Paediatric Vasculitis Activity Score (PVAS). Prospective validation provided tool reliability, reproducibility and responsiveness to change. Training of assessors was done according to the BVAS principles. Results: BVAS items were redefined (n=22) and eight paediatric items added in Cutaneous (n=4), Cardiovascular (n=3) and Abdominal (n=1) sections. The final PVAS has 64 active items in nine categories. The principles of new/worse and persistently active disease were retained as were the overall score and weighting of categories. The median PVAS in 63 children with systemic vasculitis was 4/63 (0–38/63). There was a high interobserver agreement for the overall as well as for subsystem scores (linear-weighted-κ ≥0.87). PVAS correlated with physician's global assessment (p<0.01); treatment decision (p=<0.01) and erythrocyte sedimentation rate (ESR) (p=0.01). In response to treatment, 15/19 patients assessed demonstrated a significant fall in PVAS (p=0.002), with good agreement among assessors for this change. Conclusions: The PVAS validity in children with systemic vasculitis was demonstrated. Like the BVAS, we anticipate that the PVAS will provide a robust tool to objectively define disease activity for clinical trials and future research.